Exposure to Phlebotomus perniciosus sandfly vectors is positively associated with Toscana virus and Leishmania infantum infection in human blood donors in Murcia Region, southeast Spain. Issue 5 (6th April 2022) - Ortuño, María; Muñoz, Clara; Spitzová, Tatiana; Sumova, Petra; Iborra, Maria Asunción; Pérez‐Cutillas, Pedro; Ayhan, Nazli; Charrel, Remi N.; Volf, Petr; Berriatua, Eduardo
Abstract: Antibodies against Phlebotomus perniciosus sandfly salivary gland homogenate (SGH) and recombinant protein rSP03B, sandfly‐borne Toscana virus (TOSV), Sandfly Fever Sicilian virus (SFSV) and Leishmania, as well as DNA of the latter parasite, were investigated in 670 blood samples from 575 human donors in Murcia Region, southeast Spain, in 2017 and 2018. The estimated SGH and rSP03B seroprevalences were 69% and 88%, respectively, although correlation between test results was relatively low ( ρ = 0.39). Similarly, TOSV, SFSV and Leishmania seroprevalences were 26%, 0% and 1%, respectively, and Leishmania PCR prevalence was 2%. Prevalences were significantly greater in 2017, overdispersed and not spatially related to each other although both were positively associated with SGH but not to rSP03B antibody optical densities, questioning the value of the latter as a diagnostic marker for these infections in humans.